Contribution of green manure incorporation in combination with Nitrogen fertilizer in Rice production (SAARC Journal of Agriculture, 2015)
An experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during April to November, 2012 to study the combined effects of Sesbania green manure incorporation with different levels of nitrogen fertilizer on the growth and yield of BINA dhan7. There were five treatments for using Sesbania as pre-rice green manure (GM): Fallow (No GM), GM for incorporation at 40, 50, 60, and 70 days after sowing (DAS). T. Aman was planted after chopping the GM. For T. aman there were 9 treatments: Fallow plot received full dose (180 kg urea ha-1) of N fertilizer while plots with GM received 50 and 75% of recommended N fertilizer. The experiment was laid out in a Randomized Complete Block Design with three replications. The highest grain yield of 5752 kg ha-1 and straw yield of 6654 kg ha-1 were observed in the plot treated with 75%recommended dose of nitrogen (RDN) and green manure incorporated at 50 DAS. The lowest grain yield (4783 kg ha-1) and straw yield (5154 kg ha-1) were recorded with GM incorporated at 40 DAS + 50% RDN. The N content and uptake by the grain and straw were differed significantly due to different treatments and maximum uptake was recorded with the application of 75% recommended dose of nitrogen (RDN) and green manure incorporated at 50 DAS. The overall results indicate that application of Sesbania green manure incorporated at 50 DAS in combination with 75% recommended dose of nitrogen could be considered more effective for BINA dhan7 production DOI: http://dx.doi.org/10.3329/sja.v12i2.21925 SAARC J. Agri., 12(2): 134-142 (2014)